2014
DOI: 10.1063/1.4902897
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Orientational self-ordering of spin-labeled cholesterol analogs in lipid bilayers in diluted conditions

Abstract: Lipid-cholesterol interactions are responsible for different properties of biological membranes including those determining formation in the membrane of spatial inhomogeneities (lipid rafts). To get new information on these interactions, electron spin echo (ESE) spectroscopy, which is a pulsed version of electron paramagnetic resonance (EPR), was applied to study 3β-doxyl-5α-cholestane (DCh), a spin-labeled analog of cholesterol, in phospholipid bilayer consisted of equimolecular mixture of 1,2-dipalmitoyl-sn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…ALP thus alter the plasma membrane, specifically lipid raft composition and biophysical properties (Castro et al, 2013; de Sa et al, 2015). The probe 5-DSA accumulates in biological membranes and is conventionally used to monitor membrane fluidity in studies of lipid raft organization (Grammenos et al, 2010; Kardash and Dzuba, 2014). 5-DSA can also displace certain membrane lipids and alter the function of membrane-associated proteins (Jezek et al, 1995; Wu and Gaffney, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…ALP thus alter the plasma membrane, specifically lipid raft composition and biophysical properties (Castro et al, 2013; de Sa et al, 2015). The probe 5-DSA accumulates in biological membranes and is conventionally used to monitor membrane fluidity in studies of lipid raft organization (Grammenos et al, 2010; Kardash and Dzuba, 2014). 5-DSA can also displace certain membrane lipids and alter the function of membrane-associated proteins (Jezek et al, 1995; Wu and Gaffney, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Simvastatin is a competitive inhibitor of HMG-CoA reductase, an enzyme upstream of squalene synthase in the constituent lipid biosynthesis pathway [ 70 ]. We included the small molecule 5-DSA (5-doxyl-stearic acid), a lipid probe that accumulates in biological membranes and is used to monitor membrane fluidity in lipid raft organization studies in eukaryotic cells [ 71 , 72 ]. In addition, 5-DSA is reported to displace certain membrane lipids and alter the function of various membrane-associated proteins [ 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous ESE experiments with DChl incorporated into Chol-free DOPC/DPPC bilayers have shown that DChl molecules form lipid-mediated clusters with the strong orientational correlation between the neighboring molecules. This interpretation was later confirmed by CW EPR data, which were interpreted within the model of single-crystal-like structures formed by DChl molecules in the Chol-free bilayer.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The previous ESE experiments involved extraction of the d–d contribution by comparing the ESE decays at two field positions. Here, the measurements were performed using the alternative approach, i.e., by comparing the decays for two different microwave amplitudes B 1 (see above) with the same field positionat the maximum of the EPR spectrum (position 1 in the inset to Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation